Belarusian writers at the sessions of the United Nations General Assembly (1945–1990) - Aulasenka, Ihar M. (Journal of the Belarusian State University. International Relations, 2019)
The article is devoted to the tradition of participation of Belarusian writers in the official BSSR delegations at the UN General Assembly sessions in 1945–1990. The author made an attempt to define the reasons of such a practice and to reveal the role of Belarusian writers in the BSSR official diplomacy. It is noted that the tradition of invitation of literary workers followed from the high status of writers in the social and political life of the republic. It is stated that the topics of the speeches and statements of Belarusian writers touched foremost special political questions that were determined by the bipolar struggle in the Cold War. It is showed that the documents of personal origin of writers (memoirs, epistolary heritage, and diaries) are valuable sources that help to uncover informal aspects of the everyday life of the BSSR delegation, along with the official side of its activities.
Keywords: literature; diplomacy; Byelorussian SSR; Organization of the United Nations; Cold War; General Assembly; writer; poet